(untitled) (Research, Society and Development, 2021)
With high consumption in snack bars in the city, mayonnaise is a product made from oil, water, and eggs; used to enhance the taste of food and can be found in various forms for use. In Campina Grande, a artisanal mayonnaise has been used with the addition of natural spices as a way to further attract the population’s palate, which makes this practice a propitious source for contamination of the product due to the handling process. With the objective of evaluating and quantifying the microbiological quality of this input made available by a snack bar in the city, the present study was designed. Analyzes were carried out according to the parameters governed by Normative nº 12/01, which approves technical regulation on microbiological standards in food, aiming to quantify Coliform / g (30 ° C), Salmonela spp./25g and Staphylococcus Coag. Pos /g. It was verified that all the samples of mayonnaise researched were outside one of the parameters recommended by the legislation, with the coliform being the most present microorganism. This contamination is indicative of the lack of care in handling. Thus, this study shows the importance of a microbiological analysis for the control, quality and safety in the preparation of artisanal mayonnaise, as well as the importance of good manufacturing practices to achieve food security.